Tasawuf sebagai Pendekatan Pedagogis dalam Pembelajaran Berbasis Nilai: Kajian Kepustakaan dalam Pendidikan Islam - Fuadi Fuadi; Fakhrul Rijal (LaKaspia, 2025)
Values based learning emphasizes the cultivation of students’ character, moral reasoning, and spirituality alongside cognitive achievement. In Islamic education, Sufism or tasawuf can be approached as a pedagogical lens that foregrounds self-purification or tazkiyat al-nafs, moral formation, and the meaning of knowledge as a pathway to ethical and spiritual maturity. This article examines the philosophical foundations of Sufism in Islamic education, the relevance of core Sufi values to values based learning, and their pedagogical implications for teachers and classroom practices. Using a qualitative library research design with descriptive analytical and thematic content analysis, this study synthesizes classical and contemporary literature on Sufism, Islamic pedagogy, and character education. The review indicates that key Sufi values such as sincerity or ikhlas, patience or sabar, humility or tawadhu’, ascetic self-restraint or zuhud, and muraqabah as self-awareness under divine supervision are conceptually aligned with values based learning and can be internalized through teacher role modeling, habituation, reflective learning or muhasabah, and contextual integration across subjects. Effective implementation, however, depends on teacher readiness and systematic instructional design to ensure that values education moves beyond purely normative transmission.